An interfacial reconstruction magnesium battery cathode material and methods of making and evaluating the same
Patent Information
- Application Number
- CN202611164443.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-03
- Publication Date
- 2026-10-27
AI Technical Summary
[0011]本发明旨在克服现有技术的不足,提供了一种界面重构镁电池正极材料及其制备和评估方法,解决了上述背景技术中高压镁电池正极材料与电解液的不兼容及其在高电压循环过程中出现的相变、极化和循环性能衰减等问题
[0036]本技术方案与背景技术相比,它具有如下优点:
Smart Images

Figure CN122977340A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of magnesium battery cathode material technology, specifically relating to an interface-reconstructed magnesium battery cathode material and its preparation and evaluation methods. Background Technology
[0002] Rechargeable magnesium batteries (RMBs) benefit from abundant magnesium resources (approximately 2.33 wt% in the Earth's crust) and high volumetric capacity of magnesium anodes (3833 mAh·cm⁻¹). 3 With advantages such as low redox potential (−2.37V vs. SHE), it is considered a strong candidate for next-generation high-energy-density energy storage systems. Furthermore, compared to lithium-ion batteries, Mg in traditional electrolyte systems is less prone to dendrite formation during deposition / stripping, which helps to further improve the security of RMBs.
[0003] However, divalent Mg 2+ The high charge density and strong polarization effect of cathode materials result in slow and often irreversible insertion / extraction processes. Especially under high-voltage operating conditions, cathode materials undergo significant phase transitions during cycling, which can easily lead to crystal structure collapse, resulting in a decrease in the operating voltage plateau and a shortened cycle life. This has become a key bottleneck restricting the improvement of energy density in RMBs.
[0004] Among existing cathode materials, Chevrel phase Mo6S8 is valued for its ability to store Mg. 2+ It is known for its excellent cycle stability and reversibility, but its operating voltage plateau is only about 1.1V (vs. Mg). 2+ The presence of Mg(II) content limits the overall energy density of batteries. In recent years, researchers have reported a variety of high-energy-density cathode materials, including transition metal sulfides, transition metal oxides, organic polymers, Prussian blue compounds, and polyanionic compounds. Among them, polyanionic compounds, represented by Na3V2(PO4)3 (NVP), have attracted widespread attention due to their advantages such as stable three-dimensional framework structure, low cost, good thermal stability, and fast ion diffusion channels.
[0005] Although NVP is theoretically suitable as a high-voltage cathode material, in practical systems, it cannot form an effective electrode-electrolyte interface (CEI) protective layer in the high-voltage electrolyte Mg[B(HFIP)4] / DME. This leads to hindered electrochemical reactions and poor compatibility between the cathode and the electrolyte, becoming a major obstacle to the realization of high-voltage RMBs. To improve this problem, the academic community mainly adopts the method of adding additives to the electrolyte, aiming to weaken the interaction between anions and Mg. 2+ The interaction between them. However, such strategies can only alleviate the problem at the electrolyte level and cannot fundamentally solve the structural degradation caused by phase transition and increased polarization of cathode materials under high voltage.
[0006] Therefore, it is urgent to achieve the following goals through cathode surface modification:
[0007] 1. Promotes Mg 2+ Rapid desolvation reduces interfacial impedance;
[0008] 2. Construct a stable and uniform organic-inorganic composite CEI protective layer at the interface to suppress side reactions between the electrolyte and the positive electrode;
[0009] 3. Maintain the single-phase NASICON structure of the positive electrode body unchanged to avoid capacity decay caused by phase transition.
[0010] The above approach is the key to overcoming the performance bottleneck of high-voltage rechargeable magnesium battery cathodes, and it is also the technical problem that this invention aims to solve. Summary of the Invention
[0011] The present invention aims to overcome the shortcomings of the prior art and provides an interface-reconstructed magnesium battery cathode material and its preparation and evaluation method, which solves the problems of incompatibility between high-voltage magnesium battery cathode materials and electrolytes and the phase transition, polarization and cycle performance degradation that occur during high-voltage cycling in the above-mentioned background art.
[0012] One of the technical solutions adopted by this invention to solve its technical problem is: a method for preparing an interface-reconstructed magnesium battery cathode material, comprising the following steps:
[0013] S1. Mix the transition metal solution with the complexing agent solution and react them;
[0014] S2. Heat treatment is performed on the precipitate precursor after the reaction to obtain a polyanionic compound;
[0015] S3. Mix the polyanionic compound with cysteine to obtain a mixture;
[0016] S4. The mixture is calcined under uniform heating conditions to obtain a magnesium battery cathode material with reconstructed interface; wherein the uniform heating rate is 1-10 °C / min.
[0017] In a preferred embodiment of the present invention, the entire reaction process (S1, S3) of the precursor preparation method is carried out in air under normal pressure, and the heat treatment process (S2, S4) is carried out under an argon protective atmosphere.
[0018] In a preferred embodiment of the present invention, in step S1, the transition metal in the transition metal solution is vanadium; the complexing agent contains at least one of oxalate and carbonate.
[0019] In a preferred embodiment of the present invention, in step S2, a two-stage heat treatment is adopted. The first stage heats the temperature to 350 degrees Celsius at a heating rate of 1-10 °C / min and holds it at that temperature for 3 to 5 hours. The second stage continues to heat the temperature to 800 degrees Celsius at a heating rate of 1-10 °C / min and holds it at that temperature for 6 to 8 hours.
[0020] In a preferred embodiment of the present invention, in step S1, the transition metal solution is an ammonium metavanadate solution, the carbon source is citric acid, and the sodium source is sodium carbonate; in step S3, the molar ratio of sodium to transition metal in the mixture system is 3:2.
[0021] In a preferred embodiment of the present invention, in step S4, the maximum temperature for uniform heating is 500 °C, and the holding time is 3 to 5 h. The cysteine undergoes in-situ doping of nitrogen and sulfur atoms into the surface carbon layer during the heat treatment in step S4.
[0022] The second technical solution adopted by the present invention to solve its technical problem is: providing a magnesium battery cathode material with interface reconstruction, having a single-phase structure of space group R-3c, wherein the single-phase structure is uniformly distributed inside the material; the surface of the material has a uniform ion transport layer, wherein the uniform ion transport layer is a carbon coating layer containing nitrogen and sulfur.
[0023] In a preferred embodiment of the present invention, the uniform ion transport layer is distributed on the surface of the material and has a thickness of 3.5~4.5 nm.
[0024] In a preferred embodiment of the present invention, the inner side of the uniform ion transport layer has a high charge density interface, which is characterized by a significantly higher concentration of N and S atoms than inside the material, and the NASICON single-phase structure of the main body of the material maintains structural integrity.
[0025] In a preferred embodiment of the present invention, the inner side of the uniform ion transport layer has a high charge density interface, and the interface maintains chemical interaction with the NASICON structure of the material body.
[0026] In a preferred embodiment of the present invention, the mass percentage of carbon source in the material is 1.3 wt%.
[0027] In a preferred embodiment of the present invention, the main diffraction peaks of the single-phase structure correspond completely to the standard card.
[0028] In a preferred embodiment of the present invention, the interface reconstruction of the material surface leads to the disappearance of surface cracks, the surface has a high charge density, and the bulk structure remains unchanged.
[0029] In a preferred embodiment of the present invention, the chemical formula of the material is Na3- x □ XV2(PO4)3@C-yNS (0<x<3, 0<y<1; □ represents a vacancy).
[0030] The third technical solution adopted by the present invention to solve its technical problem is: providing a composite evaluation method for verifying whether the interface-reconstructed magnesium battery cathode material achieves surface reconstruction and maintains a single phase in the bulk phase, comprising the following steps:
[0031] a) Perform copper target X-ray diffraction test on the cathode material to be evaluated to obtain an XRD pattern;
[0032] b) Simultaneously perform time-of-flight secondary ion mass spectrometry cross-section analysis and X-ray photoelectron spectroscopy test on the cathode material to obtain corresponding patterns respectively;
[0033] c) Confirm the positions of the main diffraction peaks in the XRD pattern;
[0034] d) Analyze the element distribution from the surface to the interior in the TOF-SIMS cross-section view and XPS spectrum, and confirm that nitrogen and sulfur signals only exist in the surface layer;
[0035] e) When both step c) and step d) satisfy the above determination conditions, it is determined that the cathode material has achieved interface reconstruction and the bulk phase structure maintains a single phase.
[0036] Compared with the background art, this technical solution has the following advantages:
[0037] 1. Realize interface reconstruction of single-phase polyanionic compounds: For the first time, an interface reconstruction process that maintains the R-3c single-phase structure is successfully constructed in a high-voltage cathode material for magnesium batteries, overcoming the problem of structural degradation of conventional cathodes under high-voltage cycling.
[0038] 2. Significantly improve electrochemical compatibility and cycling performance: By introducing a N, S-containing carbon coating layer on the cathode surface, the interface compatibility between the electrolyte and the cathode material is realized, the phase transition and polarization of the cathode during Mg²⁺ deintercalation / intercalation process are inhibited, the attenuation of the working voltage plateau is significantly reduced, and the cycling life and capacity retention rate are improved.
[0039] 3. Provide a fast and intuitive composite evaluation method: The evaluation system constructed by the present invention can accurately and conveniently identify whether the cathode has achieved the expected modification effect through the determination of X-ray diffraction (XRD) diffraction peaks and X-ray photoelectron spectroscopy (XPS) signal intensity, thereby providing a reliable detection means for subsequent process optimization and quality control.
[0040] Other features and beneficial effects of the present invention will be set forth in the subsequent specification. Brief Description of the Drawings
[0041] Figure 1 The refined XRD diffraction patterns of the copper target in Example 1 and Comparative Example 1 are shown.
[0042] Figure 2 The TOF-SIMS cross-sectional images and XPS spectra of the materials in Example 1 and Comparative Example 1 are shown below.
[0043] Figure 3 Scanning / transmission electron microscope images of the materials in Example 1 and Comparative Example 1;
[0044] Figure 4 The graphs show the electrochemical performance of Example 1 and Comparative Example 1 as positive electrode materials for magnesium batteries. Detailed Implementation
[0045] The present invention will be further explained below with reference to the accompanying drawings and specific embodiments.
[0046] The method for preparing the polyanionic compound interface-reconstructed magnesium battery high-voltage cathode material of the embodiment includes the following steps:
[0047] S1. Mix the transition metal solution with the complexing agent solution and react them;
[0048] S2. Heat treatment is performed on the precipitate precursor after the reaction to obtain a polyanionic compound;
[0049] S3. Mix the polyanionic compound with cysteine to obtain a mixture;
[0050] S4. The mixture is calcined under uniform heating conditions to obtain a magnesium battery cathode material with reconstructed interface; wherein the uniform heating rate is 1-10 ℃ / min.
[0051] The entire reaction process (S1, S3) of the precursor preparation method is carried out in air at normal pressure, and the heat treatment process (S2, S4) is carried out in an argon protective atmosphere.
[0052] The composite evaluation method used in this embodiment includes the following steps:
[0053] The cathode material was subjected to copper target X-ray diffraction to obtain XRD patterns; simultaneously, the cathode material was subjected to TOF-SIMS cross-sectional analysis and X-ray photoelectron spectroscopy to obtain XPS spectra.
[0054] The positions of the main diffraction peaks were determined from the XRD pattern; the elemental distribution of the material from the surface to the interior was analyzed from the TOF-SIMS cross-sectional pattern and XPS pattern.
[0055] The interface reconstruction evaluation index of the magnesium battery cathode material was determined by the fact that the positions of the main diffraction peaks did not change and no new peaks appeared; N and S element signals were present on the XPS surface, but no N and S signals were present inside the material. This was used to determine the effectiveness of the interface reconstruction polyanionic compound in the cathode material.
[0056] Example 1
[0057] 2.34 g of NH4VO3 was dissolved in 50 mL of deionized water, resulting in a milky white suspension. The solution was stirred at 80°C until it turned orange-yellow and transparent. 5.77 g of citric acid was added, and the solution changed from orange-yellow to dark blue and transparent. Then, 3.45 g of NH4H2PO4 and 1.59 g of Na2CO3 were added, resulting in a dark blue solution. After stirring at 80°C for 2 hours, the temperature was increased to 120°C to evaporate the water, resulting in a blue gel. The gel was then dried in an oven at 120°C. The resulting mixture was calcined at 350°C for 4 hours, and then calcined at 800°C for 8 hours (heating rate 5°C / min) to obtain a polyanionized compound with the chemical formula Na3V2(PO4)3@C (NVP). 1g of NVP material was mixed with 0.038g of cysteine and ground evenly. The resulting mixture was calcined at 400℃ for 5h under an argon protective atmosphere (heating rate 5℃ / min) to obtain an interface-reconstructed polyanionized compound with the chemical formula Na3V2(PO4)3@C-NS.
[0058] Comparative Example 1
[0059] 2.34 g of NH4VO3 was dissolved in 50 mL of deionized water, and the solution was a milky white suspension. The solution was stirred at 80 °C until it turned orange-yellow and transparent. 5.77 g of citric acid was added, and the solution changed from orange-yellow to dark blue and transparent. Then, 3.45 g of NH4H2PO4 and 1.59 g of Na2CO3 were added, and the solution turned dark blue. After stirring at 80 °C for 2 h, the temperature was raised to 120 °C to evaporate the water, resulting in a blue gel. The gel was then dried in an oven at 120 °C. The resulting mixture was calcined at 350 °C for 4 h and then calcined at 800 °C for 8 h (heating rate 5 °C / min) to obtain a polyanionized magnesium ion cathode material with the chemical formula Na3V2(PO4)3@C.
[0060] Figure 1The standard XRD diffraction patterns for Example 1 and Comparative Example 1 are shown. Both samples exhibited identical diffraction peaks at 14.3°, 20.2°, 23.8°, 28.8°, 31.6°, 32.1°, and 35.7°, corresponding to the (012), (104), (113), (024), (211), (116), and (300) crystal planes, respectively. These diffraction peaks are consistent with the standard trigonal NASICON phase (JCPDS No. 53-0018, space group: R-3c, lattice parameters a=7.553 Å, b=8.728 Å, c=21.804 Å). The results indicate that the synthesized NVP material possesses high crystallinity. Furthermore, Rietveld refinement data shows that the lattice parameters of the material did not change after the introduction of N / S atoms, indicating that the doping of the two heteroatoms only affects the material surface and does not alter the intrinsic crystal structure of NVP. Meanwhile, both NVP@C and NVP@C-NS maintain a NASICON-type trigonal structure (space group R-3c), with Rwp factors of 2.35% and 1.97%, respectively, confirming the reliability and accuracy of the structural analysis.
[0061] Figure 2 The TOF-SIMS cross-section and XPS spectra are shown for Example 1 and Comparative Example 1. In the TOF-SIMS depth profile, the 32S⁻ signal only appears within the surface carbon coating layer of the NVP@C-NS material, and no 32S⁻ element signal is detected inside the material. Similarly, XPS data also confirm that N / S atoms were successfully introduced into the surface carbon coating layer of the NVP material. These characterization results all indicate that N / S atoms are only doped in the surface coating layer of the NVP@C-NS material and do not affect the internal structure of the material or the valence state of V.
[0062] Figure 3 The SEM / TEM images for Example 1 and Comparative Example 1 show severe cracking on the surface of NVP@C, while no cracking is observed in NVP@C-NS. EDS elemental distribution maps show that the elements are uniformly distributed in NVP@C-NS, and N and S signals were detected. Microscopic morphology reveals that the ion transport layer thickness on the NVP@C surface is uneven, ranging from approximately 2 to 13 nm; while NVP@C-NS has a uniformly thick ion transport layer of approximately 4 nm. Both materials exhibit the same lattice fringes corresponding to the (113) crystal plane with a spacing of 0.371 nm, confirming that the modification only altered the surface ion transport layer without affecting the internal structure of NVP.
[0063] Figure 4The electrochemical performance of Example 1 and Comparative Example 1 is shown. The operating voltage plateau of the NVP@C cathode decreased significantly, with its polarization (1.18 V) being higher than that of NVP@C-NS (0.79 V) between the 40th and 200th cycles. This is because the non-uniform surface ion transport layer of NVP@C leads to non-uniform interfacial reactions, ultimately causing severe structural degradation and resulting in rapid capacity and voltage decay. 2+ During the extraction / insertion process, the operating voltage plateau of the NVP@C-NS cathode is significantly higher than that of the NVP@C cathode. At 0.5C rate, NVP@C-NS exhibits better cycle stability than NVP@C, including higher coulombic efficiency and capacity retention. The specific capacity of the NVP@C cathode after 222 cycles is only 59.8 mAh·g. ⁻1 The capacity retention was as low as 48.7%. In contrast, the NVP@C-NS cathode retained 78.7 mAh·g after 222 cycles. ⁻1 The specific capacity was high, with a capacity retention rate as high as 82.3%. These results verify that constructing a uniform surface ion transport layer in NVP@C-NS effectively suppresses the rapid decay of specific capacity and voltage.
[0064] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing an interface-reconstructed magnesium battery cathode material, characterized in that, Includes the following steps: S1. Mix the transition metal solution with the complexing agent solution and react them; S2. Heat treatment is performed on the precipitate precursor after the reaction to obtain a polyanionic compound; S3. Mix the polyanionic compound with cysteine to obtain a mixture; S4. The mixture is calcined under uniform heating conditions to obtain a magnesium battery cathode material with reconstructed interface; wherein the uniform heating rate is 1-10 °C / min.
2. The preparation method according to claim 1, characterized in that: In step S1, the transition metal in the transition metal solution is vanadium; the complexing agent contains at least one of oxalate and carbonate.
3. The preparation method according to claim 1, characterized in that: In step S2, a two-stage heat treatment is adopted. The first stage heats the temperature to 350 degrees Celsius at a heating rate of 1-10 °C / min and holds it at that temperature for 3 to 5 hours. The second stage continues to heat the temperature to 800 degrees Celsius at a heating rate of 1-10 °C / min and holds it at that temperature for 6 to 10 hours.
4. The preparation method according to claim 1, characterized in that: In step S1, the transition metal solution is an ammonium metavanadate solution, the carbon source is citric acid, and the sodium source is sodium carbonate; in step S3, the molar ratio of sodium to transition metal in the mixture system is 3:
2.
5. The preparation method according to claim 1, characterized in that: In step S4, the maximum temperature for uniform heating is 500 °C, and the temperature is maintained for 3 to 5 hours.
6. A magnesium battery cathode material with interface reconstruction, characterized in that: The material has a single-phase structure with space group R-3c, and the single-phase structure is uniformly distributed inside the material; the surface of the material has a uniform ion transport layer, which is a carbon coating layer containing nitrogen and sulfur.
7. The material according to claim 6, characterized in that: The uniform ion transport layer is distributed on the surface of the material and has a thickness of 3.5~4.5 nm.
8. The material according to claim 6, characterized in that: The carbon source accounts for 1.3 wt% of the material.
9. The material according to claim 6, characterized in that: The main diffraction peaks of the single-phase structure are (012), (104), (113), (024), (211), (116) and (300). Interfacial reconstruction on the surface of the material leads to the disappearance of interfacial cracks, which has a uniform conductive network and high charge density, while the bulk phase structure remains unchanged; the chemical formula of the material is Na3- x □ X V2(PO4)3@C-yNS, where 0<x<3, 0<y<1; □ represents a vacancy.
10. A composite evaluation method, characterized in that: To verify whether the interface-reconstructed magnesium battery cathode material achieves surface reconstruction while maintaining a single-phase bulk, the following steps are included: a) Perform copper target X-ray diffraction tests on the cathode material to be evaluated to obtain XRD patterns; b) Simultaneously, time-of-flight secondary ion mass spectrometry cross-section analysis and X-ray photoelectron spectroscopy were performed on the cathode material to obtain the corresponding spectra. c) All major diffraction peak signals were observed in the XRD pattern; d) TOF-SIMS cross-sectional images and XPS spectra were used to analyze the elemental distribution of the material from the surface to the interior, confirming that nitrogen and sulfur signals were only present on the surface and not in the interior. e) When both steps c) and d) meet the above judgment conditions, the cathode material is deemed to have achieved interface reconstruction and the bulk structure remains a single phase.